2022
DOI: 10.3390/molecules27165111
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry Leaf Extract Improves Metabolic Syndrome by Alleviating Lipid Accumulation In Vitro and In Vivo

Abstract: Metabolic syndrome (MS) is a metabolic disease with multiple complications. Mulberry leaf extract (MLE) is rich in flavonoids and has great potential in alleviating glucose and lipid metabolism disorders. This study evaluated the effect and mechanism of MLE on the alleviation of MS. The components of the MLE were analyzed, and then the regulation of lipid metabolism by MLE in vitro and in vivo was determined. In a hepatocyte model of oleic acid-induced lipid accumulation, it was found that MLE alleviated lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In addition, mulberry leaves may regulate fat deposition through the de novo fatty acid synthesis (DNL) pathway. ACC and FASN are the key genes upstream of the DNL pathway, we found that mulberry leaves had a significant inhibitory effect on ACC in backfat tissue, which may be one of the reasons for the inhibition of backfat deposition by mulberry leaves [27,28]. In addition, related studies have found that mulberry leaf polysaccharides (MLP) may increase the activity of brown adipocytes, accelerate fat consumption, and inhibit fat deposition, which may be one of the mechanisms by which MLP inhibits backfat deposition [29].…”
Section: Discussionmentioning
confidence: 72%
“…In addition, mulberry leaves may regulate fat deposition through the de novo fatty acid synthesis (DNL) pathway. ACC and FASN are the key genes upstream of the DNL pathway, we found that mulberry leaves had a significant inhibitory effect on ACC in backfat tissue, which may be one of the reasons for the inhibition of backfat deposition by mulberry leaves [27,28]. In addition, related studies have found that mulberry leaf polysaccharides (MLP) may increase the activity of brown adipocytes, accelerate fat consumption, and inhibit fat deposition, which may be one of the mechanisms by which MLP inhibits backfat deposition [29].…”
Section: Discussionmentioning
confidence: 72%
“…Many studies have found that mulberry leaf extract (MLE) is known to have therapeutic potential for numerous diseases, including diabetes, cardiovascular diseases, and cancer [ 21 , 23 ]. Furthermore, several studies have reported that MLE alleviates insulin resistance, and the active components of Morus alba L. have anti-hyperglycemic and anti-hyperlipidemic effects, suggesting a therapeutic effect on T2DM [ 24 , 25 , 26 , 27 , 28 ]. However, there have been no reports of the regulatory processes involving the IRS1/PI3K/Akt pathway in the skeletal muscle of leptin receptor-deficient db / db mice commonly used to study the T2DM mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of the induction of the prediabetic mice with HFHSD and STZ (50 mg/kg) was applied according to the previous protocol with modifications [ 8 , 29 ]. Oral glucose tolerance test (OGTT) was performed on Days 7, 14, and 21 after the STZ injection.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed according to the procedures previously published [ 29 ]. The primary antibodies used in this experiment included TLR4 (1:1000), IKKα (1:1000), p-IκBα (1:1000), NF-κB p65 (1:1000), and β-actin (1:1000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation